POLITIK BINWAS PROVINSI TERHADAP KABUPATEN/KOTA (Kasus Bangka Belitung dan Sulawesi Selatan) - Prayudi Prayudi (Jurnal Politica, 2015)
The role of Binwas in developing constructive relations among leaders from different level of government is arguably still weak. The writer reveals that the weaknesses come from relations of two factors, namely indecisiveness the central government towards the regions, and the limit of the power of governors to control regents or majors who have more authority today. This article is part of the 2014 field research conducted in the provinces Bangka-Belitung and South Sulawesi, which uses qualitative method. To cope with his finding, in the one side, the writer recommends the empowerment of political power of governors to supervise the performance of its lower officials in the regions. On the other side, he proposed punishment for regents/majors who did not follow guidance from higher government officials.